Remember Icarus! Seven risks that threaten Business Schools - Barnatt, Christopher; Starkey, Ken; Tempest, Sue (Tamkang University, 2016)
Business schools, according to certain measures, have been a major success story in the recent past of the university, enjoying significant demand growth. We suggest that their future may be more problematic. We offer different possible scenarios for business schools and identify seven key risks that they face. We argue that the most significant challenge business schools must negotiate is to redefine and clarify their mission and redesign themselves to meet these risks. We conclude that the business schools best able to survive and prosper in the future are likely to be very different from those that currently exist.